Tumor microenvironment-responsive metal nanotherapeutics for breast cancer chemo-/immunotherapy - Jinggong Liu; Wenying Li; Yongpeng Lin; Yongjun Peng; Meixiao Zhan; Haoqiang Lai; Yanzhou Chang; Yongjin Li; Ka-hing Wong; Bolai Chen; Tianfeng Chen (NPG Asia Materials, 2023)
Abstract Many metal complexes not only had excellent cytotoxic antitumor effects but also could function as a positive immunomodulatory to improve antitumor effects by modifying the local tumor microenvironment. Herein, a dual-target nanotherapeutics (MP3/ACPP/AE105@NPs) with uPAR targeting and tumor microenvironment-responsive ability was developed by using AE105 as the targeting ligand and ACPP as the tumor microenvironment-responsive peptide to locate the metal complex to cells. Assisted by the surface modification, MP3/ACPP/AE105@NPs demonstrated excellent cellular uptake of the drugs in in vitro experiments, thereby enhancing the therapeutic utility of the loaded metal complex. The nanotherapeutics induced the excessive ROS generation by inhibiting the activity of TrxR and modulated those proteins which were related to metastasis through inhibiting ERK/AKT activation mediated by FAK in MDA-MB-231 cells. This nanotherapeutics could also significantly improve the therapeutic benefits in vivo accompanied by reduced toxic side effects. Importantly, MP3/ACPP/AE105@NPs treatment stimulated immunotherapeutic response, which was indicated by the activation of tumor-infiltrated cytotoxic T cells, and improved the maturation of dendritic cells (DCs), and the proliferation-inhibitory effect of tumor-associated M2 macrophages. Taken together, the results suggested that this dual-targeted nanotherapeutics offered new opportunities for boosting the synergistic treatment of breast cancer with chemotherapy and immunotherapy.